In vitro antibacterial activity of haruan (Channa striatus bloch) fillet extracts - Mohamed, Adibah Mahirah (2012)
The use of antibacterial agent has become a standard means of treatment in management of curing diseases. Usage of antibacterial agent in health care management and curing disease is a normal and standard procedure. Many of the agents are natural products, including a highly promising one from local fresh water air breathing carnivorous fish Haruan (Channa striatus). There are several products derived from Haruan available in market and commonly consumed after surgical intervention and caesarian mother. Nowadays the Haruan product comes out with various forms such as in tablet (Har-One brand), soup (Rizza brand) and essence of Haruan (Maspati, Harwany and Polleney brands). The species is an ethnopharmacology for wound healing, and this study was conducted to investigate antibacterial activity of the fish through in vitro systems, as part of a research development drug discovery program. This study focuses on antibacterial activity of five different extracts from Haruan fillet against selected pathogenic and good bacteria using disc diffusion, agar well and broth microdilution assay. The antibacterial test using Haruan Traditional Extract Upper Phase (HTEA), Haruan Traditional Extract Lower Phase (HTEL) and Haruan Aqueous Extract (HAE) showed significant result (P<0.05) compared to commercial standard antibiotics through disc diffusion assay and agar well assay against Helicobacter pylori ATCC 43579, Salmonella typhimurium ATCC 14028 and Escherichia coli ATCC 25922. The broth microdilution assay revealed moderate to strong activity with minimum inhibition concentration (MIC) and minimum inhibition concentration required to inhibit 50 percent of bacteria (MIC50) values through HTEA, HTEL and HAE. The HTEA gave the greatest MIC values with 25 μg/ml against H. pylori ATCC 43579. On the other hand, the same extract also showed the highest antibacterial effect against H.pylori ATCC 700824 and H.pylori ATCC 43579 with MIC50 values were 73.54 and 66.89 g/ml. Furthermore, the HAE gave moderate effects with 93.15 and 77.19 g/ml of MIC50 values on the same bacteria. In contrast, the other extracts such as Haruan Chloroform Extract (HCE) and Haruan Methanol Extract (HME) showed very mild activity against bacteria tested. The outcome obtained from this study suggested that polar solvent aqueous extract of Haruan demonstrated good antibacterial activity and showed great potential in treatment of gastrointestinal infection disease cause by H pylori bacteria.